Tobacco extract-based biopesticide from cigarette butt waste for corn plants (Zea mays L.) - Nurhidayah Nurhidayah; Taufik Abdullah; Hijriati Sholehah; Fairuz Safhira (Jurnal Pijar Mipa, 2022)
Cigarette butt waste can be used for biopesticides for environmentally friendly agricultural activities. Biopesticides cigarette can be produced by conducting a maceration extraction test using polar, non-polar, and semi-polar compounds and conducting a Mass Spectrometer Chromatography (GC-MS) test. This study aims to determine the effectiveness of bio-pesticide based on tobacco extract from cigarette butt waste for maize (Zea mays L.)". The highest yield value was the ethanol sample of 1.208%, compared to the N-hexane sample of 0.25% and the DCM sample of 0.6%. For the comparison of solvents used were 500 ml of ethanol, 250 ml of N-hexane, and 250 ml for DCM as well. After conducting the GC-MS test, the compounds obtained are alkaloid compounds, phenolic compounds, sesquiterpenoid compounds, and terpenoid compounds, each of which has benefits as a pest control or deterrent to plants. For the effectiveness test results on Corn (Zea mays L.), there was no intensity of pest attack on the ethanol sample, N-hexane sample, and DCM sample. In contrast, there was a pest attack intensity of 0.3% for the control sample. Therefore, the Biopesticides studied are similar to synthetic pesticides because they can eradicate pests and make growth effective faster.